Autosomal dominant lateral temporal epilepsy in a family exhibiting a rare heterozygous mutation and deletion in the leucine-rich glioma inactivated 1 gene. (21st June 2022) - Liu, Jie; Hu, Danmei; Zhang, Zhijuan; Tang, Fenglin; Yan, Yin; Ma, Yuanlin
Highlights: An unreported missense mutation of LGI1 was found in the whole exome sequencing of the epilepsy family. A new LGI1 mutation inhibits the development of hippocampal neurons. Mutation in the LGI1 alter the secretion function of proteins. Abstract: Autosomal dominant lateral temporal epilepsy (ADLTE) is an inherited syndrome caused by mutations in the leucine-rich glioma inactivated 1 ( LGI1 ) gene. In a family with six ADLTE patients spanning four generations, our linkage and exome sequencing investigations revealed a rare frameshift heterozygous mutation in LGI1 (c.1494del(p.Phe498LeufsTer15)). Gene cloning methods were used to create plasmids with wild-type and mutant LGI1 alleles. Through transfection of HEK293 cells and primary neurons, they were utilized to assess the subcellular location of wild-type and mutant LGI1. Moreover, the plasmid-transfected primary neurons were analyzed for neuronal complexity and density of dendritic spines. According to our results. the mutation decreased LGI1 secretion in transfected HEK293 cells. In primary neurons, mutant LGI1 affected neuronal polarity and complexity. Our findings have broadened the phenotypic spectrum of LGI1 mutations and provided evidence regarding the pathogenicity of this mutation. In addition, we discovered new information about the role of LGI1 in the development of temporal lobe epilepsy, along with a possible link between neuronal polarity disorder and ADLTE.